The Severity Level of Knee Osteoarthritis is a Predictor of Falls Among the Elderly - Rosidah, Nikmatur; Rosita Mudhari, Dewi Nanda; Ika Wardojo, Sri Sunaringsih (Jurnal Kesehatan Masyarakat, 2024)
Knee osteoarthritis is the most common degenerative disease that leads to the disability in elderly. Changes in the joint structure that cause pain, functional limitations, and decreased the quality of elderly life. Muscle weakness and decreased proprioception associated with the decrease of balance can cause someone with Knee OA to have an increase the risk of falling. This study aimed to determine whether the severity level of knee OA is interdependent with the risk of falls among the elderly. Cross-sectional study an observational analytic approach, carried out at University Hospital of Muhammadiyah Malang, in May 2023. The sample consisted of 30 elderly subjects recruited and used purposive sampling for a clinical trial. Oxford Knee Score (OKS) is used to measure the severity of KOA and the Morse Falls Scale (MFS) is used to measure the risk of falls of the elderly. The correlation between the severity of knee OA and the risk of falls was identified through the Fisher exact test. Among 30 subjects with knee OA. The prevalence of knee OA with poor joint function was 20%. There is a relationship between the degree of KOA and the level of fall risk. The results of this study show that there is a relationship between the degree of KOA and the level of risk of falls in the elderly at UMM Hospital where, the higher the degree of KOA, the higher the level of risk of falls in the elderly.